Removal of suspended solids from weathered tungsten-ore beneficiation wastewater by electroneutralization and chemical precipitation. (1st November 2021) - Zhai, Qilin; Lu, Hongyu; Liu, Runqing; He, Dongdong; Wang, Changtao; Sun, Wei
Highlights: CaCl2 could remove suspended solids in weathered tungsten-ore beneficiation wastewater. The Ca 2+ supplied by CaCl2 can neutralize the negative charge on suspended solids' surface. CaCO3(S) and CaSiO3(S) were formed by the reaction of Ca 2+ with CO3 2– and SiO3 2– in wastewater. The reuse of treated water into tungsten-flotation system did not affect flotation index. Abstract: The direct reuse of weathered tungsten-ore beneficiation wastewater (WTBW) in tungsten-flotation system seriously deteriorates the flotation index of tungsten because of its high content of suspended solids (SS). In the present study, an innovative technology using calcium chloride (CaCl2 ) to remove SS from WTBW was established based on the theory of electroneutralization and chemical precipitation. A series of laboratory tests was performed to determine the optimal conditions for SS removal from WTBW. Species-distribution calculation, zeta potential, X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy were used to analyze the underlying mechanism. Results showed that the content of SS in WTBW decreased from 25.16 × 10 3 mg/L to 22.56 mg/L after CaCl2 treatment. A concentrate with tungsten grade and recovery of 1.93% and 74.81%, respectively, was obtained by reusing the treated wastewater in the tungsten-flotation system. Compared with untreated wastewater, the tungsten grade and recovery of concentrate increased by 0.45% and 12.20%, respectively. Moreover, the Ca 2+ supplied by CaCl2 can neutralize the negative charge on SS surface and further react with CO3 2– and SiO3 2– in solution to form CaCO3(S) and CaSiO3(S), which explained why CaCl2 can promote the aggregation and sedimentation of SS.